Assessment of Dendrogeomorphological Dating Methods of Past Geomorphic Processes in the Aktru Headwater (the Russian Altai Mountains) - S. Nikolaeva A.; D. Savchuk A.; С. Николаева А.; Д. Савчук А. (Izvestiya Rossiiskoi Akademii Nauk Seriya Geograficheskaya, 2021)
At the present, the dendrogeomorphological methods are widespread to date the past geomorphic processes. In areas that are poorly studied in this regard, they need to be tested for the effectiveness of their use. The article’s goal is to evaluate the dendrogeomorphological methods of the past geomorphic events dating in the Aktru headwater (the Severo-Chuisky Range, the Russian Altai Mountains). The peculiarities of the methods were considered, and their effectiveness was evaluated for dating the past debris flows and snow avalanches in the debris flow torrent and snow avalanche path. The injury and the radial increment dendroindications were main and anatomical (tree-rings saturated by resin) and age dendroindications were additional. The non-dendrogeomorphological methods of detection and dating of the past geomorphic events (eyewitnesses, soil profiles, radiocarbon analyses, etc.) appeared to be especially useful. The use of all these methods in a complex made it possible to increase both the past events detection and the accuracy and reliability of their dating. In the debris flow torrent, 13 events (6 debris flows, 5 snow avalanches, 1 wildfire, and 1 unidentified event) were dated during 220 years before the present. In the snow avalanche path, 20 avalanches were dated during 65 years before the present. При датировании вызванных экзогенными гравитационными процессами (ЭГП) событий прошлого широкое распространение в настоящее время получили дендроиндикационные методы. Они наиболее информативны на малоизученных горных территориях, где нуждаются в проверке эффективности их использования. Цель – оценить применяемые в дендроиндикационных исследованиях методы датирования таких событий в конкретных горных условиях – верховьях р. Актру (Северо-Чуйский хребет, Горный Алтай) на примере селевого бассейна и лавинного комплекса. Возрастная и анатомическая (заcмоленные кольца) индикации позволили выявить и датировать события приблизительно (периоды времени до нескольких десятков лет), травматическая и дендрометрическая – точно (год), недендроиндикационные методы – уточнить их (размеры, вид и год). Комплексное использование всех этих методов способствовало более полному выявлению событий в прошлом, повышению точности и достоверности их датирования. В селевом бассейне за последние 220 лет датировано 13 событий, в том числе 6 селей, 5 лавин, 1 пожар, в лавинном комплексе за последние 65 лет – 20 лавин.